a) 7.x - 4 = 5.x + 6 *
x =10/11
x = - 1
x = 5
n.d.a
b) 5.x - 13 = 7.x - 19 *
x = - 3
x = 3
x = - 16
n.d.a
c) 4.( x - 2 ) - 2.( x - 1 ) = 10 *
x = 8
x = - 8
x = - 2
n.d.a
d) *
Imagem sem legenda
x = -2
x = -8
x = 8
x = -6
n.d.a
Anexos:
![](https://pt-static.z-dn.net/files/de7/20ce53559da00724d1a32aba66c91452.png)
Soluções para a tarefa
Respondido por
0
Resposta:
hixicg66zr fielmente
Explicação passo-a-passo:
Byron
Perguntas interessantes
Matemática,
8 meses atrás
Geografia,
8 meses atrás
Artes,
9 meses atrás
Matemática,
9 meses atrás
Física,
1 ano atrás
História,
1 ano atrás